Characteristics of defensin1 gene and designing structure to create resistant transgenic corn lines to weevils - Thủy, Vì Thị Xuân; Thu, Lò Thị Mai; Tường, Hồ Mạnh; Sơn, Lê Văn; Thanh, Nguyễn Vũ Thanh; Mậu, Chu Hoàng (Vietnam Journal of Biotechnology, 2016)
Plant defensins are multifunctional proteins, inhibiting the growth of fungal, anti-bacterial, altering membrane channels, inhibiting activity of trypsin and α-amylase. Plant defensin consists of 18 groups in which the group 1 includes  defensins to inhibit either α-amylase enzyme or trypsin. Defensins bind to the active site of α-amylase in the weevil gut, thus inhibit starch digestion in weevils. In this report, we present the results of cloning and determining the ZmDEF1 gene sequence isolated from mRNA and DNA of Sonla province local maize and LVN99 hybrid maize cultivar. The coding region of ZmDEF1 gene isolated from some maize samples had the size of 243 nucleotides, encoding 80 amino acids. Gen ZmDEF1 isolated from DNA had the size 345bp consists of two exons and one in tron (102 bp). The nucleotide sequences of ZmDEF1 gene (DNA) of the samples have 6 positions nucleotide difference, on exon 1 has two points difference (position 43, 53), on intron has a difference (position 150), on exon 2 has 3 nucleotide site difference (203, 263 and 297 position). Deduced amino acid sequences of defensin of the Sonla local maize sample has 8 cysteines to make 4 disulfide bridges, while LVN99 hybrid maize has 7 cysteines, which can formed only 3 disulfide bridges. Transformation vector pBetaPhaso-ZmDEF1 has been designed successfully, in which ZmDEF1 is controlled by seed specific Phasoline promoter. The correct insertion and expression of ZmDEF1 was examinated in transgenic tobacco plants throught PCR and RT-PCR, respectively. These results provide an firm evident for using the designed transformation vector to produce transgenic maỉze lines with an improved resistant ability  to weevils.